TikTok Social Media: A Breakthrough to the Moderation in Da’wah Education - Muhamad Basyrul Muvid; Didiet Anindita Arnandy; Achmad Arrosyidi (AL-ISHLAH: Jurnal Pendidikan, 2024)
TikTok as a social media, nowadays is increasingly used for various purposes including video content about religion, such as Da’wah. It is an effective choice to disseminate moderate da'wah for the process of educating (tarbiyah) the community to become smart, wise, and polite people who can implement their spiritual and social responsibilities. The research method in this study used a qualitative type using a literature study approach, with data collection techniques of documentation on TikTok videos, and data analysis techniques using induction, interpretation, and comparison. The results of this study show that the moderation in da'wah education on TikTok has gained an extensive scope in the public view and the enthusiasm of the community to learn Islam or "ngaji" has increased. Among the preachers with moderate da'wah education on TikTok are Gus Iqdam, Gus Kautsar, and Neng Umi Laila, who always carry out the process of education (coaching) to the community with a humanist, contextual, and dialectical da'wah model with straightforward rhetoric, hamble and packed with light language so that it is easily accepted by all circles. Their da'wah ideology is based on ahlussunnah which is very compatible with the spirit of togetherness in Indonesia, so they acquire a positive response from the audiences. This reinforces that the digitalization of da'wah on social media is a powerful and quick strategy in the process of educating people to practice religion in a friendly, peaceful, and full of togetherness amid diversity.